Social scientists meet the media - Haslam, Cheryl, 1960-; Bryman, Alan (Routledge, 1994)
Social Scientists Meet the Media collects the experiences of academics who have sought to publicize their research. It contains accounts from social scientists and representatives from radio, television and the press.